Effect of adding Scutellaria baicalensis Georgi to feed on the microbial diversity in cattle feces - Junli Zhang; Xue Bai; Fen Li; Rina Na; Yun Ma; Xiaojun Liang (Frontiers in Microbiology)
IntroductionInflammation and oxidative stress can seriously endanger the health and growth of beef cattle. Scutellaria baicalensis Georgi (SB) has significant anti-inflammatory and antioxidative effects. However, studies on the application of SB stems and leaves as roughage in animal husbandry are limited. Therefore, in this study, we investigated the effects of adding different proportions of SB stems and leaves to roughage on the microbial diversity of bovine feces.MethodsIn total, 20 cattles (Simmental xlocal yellow cattle) were randomly divided into four groups: CON, G1, G2, and G3 (with 3%, 6%, and 9% SB stems and leaves added to the roughage, respectively). All cattles were exposed to pre-experimental conditions for 15 days and experimental conditions for 90 days. Growth performance indicators were measured on the 0th, 15th, 45th, and 90th days of the formal experiment. Blood was collected for measuring biochemical performance indices. Fresh fecal samples were collected on the 90th day for 16S sequencing to study the microbial diversity of cow feces.ResultsThe results showed that during the experiment, the F/G of the G1, G2, and G3 groups was significantly lower than that of the CON group (P < 0.05). The IL-10 content in the serum of the G3 group was significantly greater than that in the CON group (P < 0.05). The 16S rRNA results revealed significant differences in the composition of the bacterial community between the SB groups and the CON group. At the phylum level, adding the stems and leaves of SB significantly decreased the Firmicutes/Bacteroidetes ratio, and the relative abundances of Spirochaetes, Verrucomicrobia, and Proteobacteria decreased. At the genus level, Anaerovibrio, Epulopiscium, Akkermansia, Bacteroides, YRC22, Paludibacter, 5-7N15, Butyrivibrio, Prevotella, and Anaeroplasma were identified as markers of intergroup differences. These intergroup differential microbiota were associated with pathways such as amino acid biosynthesis, fatty acid and lipid biosynthesis, carbohydrate biosynthesis, carbohydrate degradation, nucleoside and nucleotide degradation, fermentation, glycolysis, the TCA cycle, glycan biosynthesis, and glycan degradation.DiscussionOur findings revealed that adding the stems and leaves of SB to feed can promote body growth and antioxidant capacity and increase the diversity of the gut microbiota. This new feeding strategy can improve the efficiency of cattle farming.